Double response of glaciers in the Upper Peio Valley (Rhaetian Alps, Italy) to the Younger Dryas climatic deterioration. (21st September 2017) - Baroni, Carlo; Casale, Stefano; Salvatore, Maria Cristina; Ivy‐Ochs, Susan; Christl, Marcus; Carturan, Luca; Seppi, Roberto; Carton, Alberto
Abstract : A pronounced climate reorganization characterized the Lateglacial–Holocene transition in the Northern Hemisphere. Glaciers in the Alps reacted to the last climate deterioration at the end of the Late Pleistocene leaving landscape features suitable for reconstructing Lateglacial and early Holocene history. In this context, the Upper Peio Valley in the Ortles‐Cevedale Group (Rhaetian Alps, Italy) has well‐preserved moraines of La Mare Glacier and Careser Glacier, which we used to reconstruct the glaciers' behaviour and to investigate the Lateglacial–Holocene transition. Detailed glacier reconstructions combined with 11 new 10 Be exposure ages allow dating of the response of these glaciers to the Younger Dryas (YD) cold event. La Mare and Careser glaciers reacted to the YD with a double response, building two clear moraine sets. Data from La Mare Glacier indicate the first advance occurred prior to 12.3±0.7 ka (before 10.0±0.7 ka at Careser Glacier). Both glaciers then re‐advanced before 11.2±0.8 ka as dated at La Mare Glacier. This phase can be interpreted as the Egesen stadial glaciers' expression of the end of the YD. Morphometric parameters of the reconstructed phases allowed the estimation of areal and volumetric variations of the studied glaciers as well as equilibrium line altitude (ELA). ΔELA with respect to the Little Ice Age (LIA) maximum position are −225 m for La Mare Glacier and −180 m for the Careser Glacier. Although the behaviour of the two glaciers showed coherence during the Egesen stadial and the LIA, they have behaved individually since then. La Mare has lost 60% of its area, while Careser has lost 85% since the latest Pleistocene. We attribute this to the greater proportion of ice at high elevation of the La Mare Glacier, underlining the importance of bed hypsometry in glacier response.